2016
DOI: 10.1039/c6sc02623k
|View full text |Cite
|
Sign up to set email alerts
|

Competition between drum and quasi-planar structures in RhB18: motifs for metallo-boronanotubes and metallo-borophenes

Abstract: Two nearly degenerate isomers, one a drum and the other quasi-planar, are discovered for the gaseous RhB18 – cluster, revealing a competition between the metallo-boronanotube and metallo-borophene structures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
63
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 106 publications
(64 citation statements)
references
References 48 publications
0
63
0
1
Order By: Relevance
“…[20][21][22][23][24] The finding of the planar CoB 18 − cluster, in which the Co dopant becomes a part of the 2D plane, has led to the possibility of metalloborophenes. [25][26][27][28] Recently, we have found that di-lanthanide The Journal of Chemical Physics ARTICLE scitation.org/journal/jcp octaboron clusters (Ln 2 B 8 − ) can form remarkable inverse sandwiches. 29 There have been few experimental studies of boron clusters doped by group V elements except B n N − (n = 1-3).…”
Section: Introductionmentioning
confidence: 99%
“…[20][21][22][23][24] The finding of the planar CoB 18 − cluster, in which the Co dopant becomes a part of the 2D plane, has led to the possibility of metalloborophenes. [25][26][27][28] Recently, we have found that di-lanthanide The Journal of Chemical Physics ARTICLE scitation.org/journal/jcp octaboron clusters (Ln 2 B 8 − ) can form remarkable inverse sandwiches. 29 There have been few experimental studies of boron clusters doped by group V elements except B n N − (n = 1-3).…”
Section: Introductionmentioning
confidence: 99%
“…In the past two decades, extensive experimental and theoretical studies have been conducted to elucidate the structures and chemical bonding of size-selected boron clusters (7-11), resulting in the discoveries of novel graphene-like (borophene), fullerene-like (borospherene), and nanotubular structures (12-16). However, there has been relatively less attention devoted to metal boride clusters, even though a number of transition metal-doped clusters have been characterized (11,(17)(18)(19). In particular, there have been few experimental studies on lanthanide boron clusters.The SmB 6 − and PrB 7 − clusters represent the first lanthanide (Ln) boron clusters reported (20, 21), each featuring a B 6 or B 7 cluster coordinated to the Ln atom.…”
mentioning
confidence: 99%
“…In the past two decades, extensive experimental and theoretical studies have been conducted to elucidate the structures and chemical bonding of size-selected boron clusters (7)(8)(9)(10)(11), resulting in the discoveries of novel graphene-like (borophene), fullerene-like (borospherene), and nanotubular structures (12)(13)(14)(15)(16). However, there has been relatively less attention devoted to metal boride clusters, even though a number of transition metal-doped clusters have been characterized (11,(17)(18)(19)…”
mentioning
confidence: 99%
“…Additionally, in the planar B 7 Au 2 – and B 7 H 2 – clusters, the two Au (H) atoms are anchored at the terminal B atoms; this can be understood by the similarity of the chemistry of gold and hydrogen atoms , . In the case of a doping transition‐metal (TM) atom, many transition‐metal‐doped boron clusters are observed to prefer structures with highly coordinated metal atoms occupying the central position of the boron ring . The perfectly planar C 2 v structure has been found to be the global minimum of the Co∈B 18 – cluster, which consists of a planar boron monolayer with a central Co atom .…”
Section: Introductionmentioning
confidence: 99%